A comparative analysis on Finnish and Korean high school English textbooks in the perspective of communicative language teaching - Namgung, Wook (2016)
English textbooks are a key resource for English courses in both Finnish and Korean high schools. The present study aims to compare the similarities and differences of Finnish and Korean high school English textbooks and analyze them from the perspective of Communicative Language Teaching (CLT) on which English textbooks of both countries are theoretically based. Two English textbooks have been selected from each country for this research. One textbook is targeted for 10th grade and the other for 11th grade. The textbooks have been analyzed according to six dimensions: textbook structure, vocabulary, language forms, topics and cultural backgrounds, communicative functions, and activities for language skills. The study conducts a quantitative content analysis for the comparison of English textbooks of both countries and a qualitative theory-driven content analysis through the lens of CLT. The findings show a variety of similarities and differences between Finnish and Korean textbooks in the six dimensions. The results provide some implications for communicative textbooks from the perspective of CLT. The impact of the national testing system on English textbook design was discussed on the basis of the findings. This study suggests the reconsideration of the current vocabulary control for English textbooks in the Korean national curriculum and the substitution for the translation works noticeably visible in Finnish textbooks for CLT. The findings can provide English teachers with pedagogical benefits and the textbooks publishers with insights for textbook design. These findings also give some academic ideas on how diversely CLT can be realized in English textbooks.